The Contribution of Islamic University Malang as Islamic Private Higher Education in Developing Islamic Civilization - Lina Agustina (Didaktika Religia, 2019)
This article aims to examine the contribution of Islamic University Malang (Unisma) as a private Islamic tertiary institution in developing Islamic civilization in Indonesia. To be more focused, the author limits the discussion to improving the quality of lectures and the concept of Islamization of science in building Islamic civilization in Indonesia. This article uses a qualitative approach and explores Malang Islamic University as an object of study. The results of the study show that improving the quality of lectures at Unisma as a private Islamic tertiary institution can be done in various ways. The strategies used in the lecture process are based on andragogical values that are relevant to the needs of students. The principles of lectures prioritize the potential of students and are directed towards the development of cognitive, affective, and psychomotor aspects of students in a balanced manner. Unisma, as a private Islamic tertiary institution, demonstrates its capabilities in developing Indonesian Islamic civilization. This can be seen from the increasing number of institutional cooperation with various institutions both from within and outside the country. Unisma is also the only campus in East Java that carries the values of multicultural education. This is evidenced by the implementation of a multicultural PAI doctoral program and many Unisma students who come from various ethnic groups, religions and classes. Moreover, campus policies also lead to the empowerment of graduates. Unisma graduates are truly empowered optimally in accordance with their respective field. Thus, the spirit of intellect and religiosity can penetrate in various lines of Islamic civilization